Accumulation of persistent organic pollutants in trout from the Canadian Rocky Mountains - Demers, Marc J (University of Ottawa (Canada), 2006)
The accumulation of persistent organic pollutants (POPs) in mountain regions was investigated by collecting trout from eight lakes spanning an elevation gradient of 760 to 2360 m.a.s.l. in the Canadian Rocky Mountains. All lakes were located within (or close to) national parks in Alberta and British Columbia. Concentrations of several organochlorine compounds increased significantly with lake elevation. The compounds, which increased the most with elevation, were the less volatile organochlorine pesticides (OCPs) (e.g. dieldrin, DDTs). The relationship was not as strong for the more volatile organochlorines (e.g. HCHs, HCB). Biological factors such as growth dilution of contaminants appears to be a major determinant of contaminant concentrations of organochlorine compounds in alpine lakes. Principal component analysis (PCA) showed that POP composition in trout relate strongly to octanol/water partition co-efficient (Kow) and lake elevation.
Keywords: Biology, Ecology.